N2–H2 capacitively coupled radio-frequency discharges at low pressure. Part I. Experimental results: effect of the H2 amount on electrons, positive ions and ammonia formation. (24th August 2020) - Chatain, Audrey; Jiménez-Redondo, Miguel; Vettier, Ludovic; Guaitella, Olivier; Carrasco, Nathalie; Alves, Luis Lemos; Marques, Luis; Cernogora, Guy
Abstract: The mixing of N2 with H2 leads to very different plasmas from pure N2 and H2 plasma discharges. Numerous issues are therefore raised involving the processes leading to ammonia (NH3 ) formation. The aim of this work is to better characterize capacitively-coupled radiofrequency plasma discharges in N2 with few percents of H2 (up to 5%), at low pressure (0.3–1 mbar) and low coupled power (3–13 W). Both experimental measurements and numerical simulations are performed. For clarity, we separated the results in two complementary parts. The actual one (first part), presents the details on the experimental measurements, while the second focuses on the simulation, a hybrid model combining a 2D fluid module and a 0D kinetic module. Electron density is measured by a resonant cavity method. It varies from 0.4 to 5 × 10 9 cm −3, corresponding to ionization degrees from 2 × 10 −8 to 4 × 10 −7 . Ammonia density is quantified by combining IR absorption and mass spectrometry. It increases linearly with the amount of H2 (up to 3 × 10 13 cm −3 at 5% H2 ). On the contrary, it is constant with pressure, which suggests the dominance of surface processes on the formation of ammonia. Positive ions are measured by mass spectrometry. Nitrogen-bearing ions are hydrogenated by the injection of H2, N2 H + being the major ion as soon as the amount of H2 is >1%. The increase of pressure leads to an increase of secondary ions formed by ion/radical–neutral collisions (ex: N2 H +, NH4 +, H3 + ), while an increase of the coupled power favours ions formed by direct ionization (ex: N2 +, NH3 +, H2 + ).